ANALISIS KETAHANAN MINYAK DI 15 NEGARA PENGIMPOR MINYAK TAHUN 2010 - Andry Satrio Nugroho (Center for Economic Studies Universitas Katolik Parahyangan, 2015)
Energy security is defined as the ability of an economy to provide sufficient, affordable and environmentally sustainable energy services so as to maintain a maximum welfare of the state. Despite the widespread use of the energy security concept, it doesn’t have a regular indicator to measure energy security; so this causes bias in determining the direction of energy policy. Oil Vulnerability Index _OVI) could be used as an indicator which can assess energy security, particularly in oil. This study aims to estimate oil security in 15 oil importer countries in 2010 using OVI. The results show that most countries have oil security problem. Asia is the region that has low level of oil security than other regions. Indonesia is one of the countries that has low level of oil security. Fuel subsidy is considered to have large contribution causing a low level of oil security in Indonesia.